2021
DOI: 10.1186/s12864-021-07642-x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolome and transcriptome profiling reveals anthocyanin contents and anthocyanin-related genes of chimeric leaves in Ananas comosus var. bracteatus

Abstract: Background Ananas comosus var. bracteatus is a colorful plant used as a cut flower or landscape ornamental. The unique foliage color of this plant includes both green and red leaves and, as a trait of interest, deserves investigation. In order to explore the pigments behind the red section of the chimeric leaves, the green and red parts of chimeric leaves of Ananas comosus var. bracteatus were sampled and analyzed at phenotypic, cellular and molecular levels in this study. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 64 publications
1
18
0
Order By: Relevance
“…bracteatus based on our published RNA-seq data (BioProject accession no. PRJNA720713) [ 40 ]. The transcripts of eight AbR2R3-MYB genes were not detected in these nine samples, which suggested that they were pseudogenes or poorly expressed in these samples ( Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…bracteatus based on our published RNA-seq data (BioProject accession no. PRJNA720713) [ 40 ]. The transcripts of eight AbR2R3-MYB genes were not detected in these nine samples, which suggested that they were pseudogenes or poorly expressed in these samples ( Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…Anthocyanin biosynthesis is a very important aspect of the colors of the fruit, leaves, and bracts of var. bracteatus ( Zhou et al 2021 ) and for stress response ( Sarma et al 1997 ; Gould and Quinn 1999 ; Ahmed et al 2015 ). The accumulation of anthocyanin results from phenylpropanoid biosynthesis and flavonoid biosynthesis, and the functions of certain structural genes determine the biosynthesis of anthocyanins.…”
Section: Resultsmentioning
confidence: 99%
“…Reports show that the accumulation of anthocyanins is closely related to resistance to biotic stress due to insects and diseases, and abiotic stress such as high light or low temperature ( Sarma et al 1997 ; Gould and Quinn 1999 ; Ahmed et al 2015 ). The decreased chlorophyll content and incomplete chloroplast development of the chimeric leaves of GL1 result in changes in photosynthesis ( Li et al 2017 ; Xue et al 2019 ; Mao et al 2020 ; Zhou et al 2021 ). Similar to most pineapple [ A. comosus (L.) Merr. ]…”
Section: Introductionmentioning
confidence: 99%
“…This variation can be used as important material for the development and cultivation of new varieties for D. delavayi . In recent years, the metabolome and transcriptome have been widely used to breed various plants by combining the gene data in the transcriptome with the phenotypic profiles in the metabolome as well as to enrich metabolic pathways and molecular interactions to screen for key metabolic pathways or genes and to carry out in-depth analyses and validation on metabolites [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%